2003
DOI: 10.1038/nm944
|View full text |Cite
|
Sign up to set email alerts
|

Multiple actions of systemic artemin in experimental neuropathy

Abstract: The clinical management of neuropathic pain is particularly challenging. Current therapies for neuropathic pain modulate nerve impulse propagation or synaptic transmission; these therapies are of limited benefit and have undesirable side effects. Injuries to peripheral nerves result in a host of pathophysiological changes associated with the sustained expression of abnormal pain. Here we show that systemic, intermittent administration of artemin produces dose- and time-related reversal of nerve injury-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
178
5
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(198 citation statements)
references
References 46 publications
14
178
5
1
Order By: Relevance
“…Species difference is a confounding factor, because both published studies were conducted in rats. Gardell et al (2003) reported no change in thermal or mechanical paw sensitivity after subcutaneous artemin injection in the rat (the site of injection was not specified), but they did not test thermal hyperalgesia at the site of artemin injection, as in the experiments reported here. Perhaps the acute affects of artemin we observed represent local action of artemin on nociceptors in the glabrous skin that was directly tested in the Hargreaves apparatus.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Species difference is a confounding factor, because both published studies were conducted in rats. Gardell et al (2003) reported no change in thermal or mechanical paw sensitivity after subcutaneous artemin injection in the rat (the site of injection was not specified), but they did not test thermal hyperalgesia at the site of artemin injection, as in the experiments reported here. Perhaps the acute affects of artemin we observed represent local action of artemin on nociceptors in the glabrous skin that was directly tested in the Hargreaves apparatus.…”
Section: Discussionmentioning
confidence: 84%
“…Perhaps the acute affects of artemin we observed represent local action of artemin on nociceptors in the glabrous skin that was directly tested in the Hargreaves apparatus. Also, Gardell et al (2003) used artemin concentrations that were 300 times greater than that used in this study; this difference raises the possibility that high artemin concentrations have other effects that mask the hyperalgesic action reported here. However, in contrast to Gardell et al (2003), a similar study found that artemin injection [either intraperitoneally (5 m/kg) or intrathecally (10 g/d)] in rats did not block hyperalgesia produced by spinal nerve ligation (Bolon et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…At present, few drugs are effective in treating neuropathic pain, and their efficacy is only demonstrated in Յ30% of patients (Woolf and Mannion, 1999;Gardell et al, 2003). However, all current drugs were developed or considered to act against molecular targets in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth member of the GFL family, artemin, has survivalpromoting effects on dopaminergic neurones in culture [98] and in vivo [99], and also has potent actions on sensory neurones of the dorsal root ganglia [98]. Like persephin, artemin has not progressed into clinical trials for PD; however it has been tested as a therapeutic for neuropathy [100].…”
Section: Effects Of Persephin and Artemin In Vitro And In Vivomentioning
confidence: 99%